DETERMINING FACTORS OF A CITY’S TOURISM ATTRACTIVENESS - ARTURO CALVO-MORA; JUAN MANUEL BERBEL-PINEDA; RAFAEL PERIÁÑEZ; EVA MARÍA SUÁREZ (Tourism & Management Studies)
The primary aim of this work is to identify actions that can improve the tourist attractiveness of a city, specifically Seville, and secondly, to test the Concept Mapping methodology when it is applied to the conceptualization of complex constructs associated with tourism management. This methodology combines qualitative information provided by experts and quantitative information obtained from multivariate statistical techniques. The results of the work suggest, in addition to the validity and suitability of the methodology, that the attractiveness of a tourist destination could be improved by the implementation of a set of publicprivate plans linked to its tourism positioning, residents‟ awareness, the best use of the cultural and social wealth and the rich heritage, as well as the improvement of the infrastructure and the public and private management of tourism.